2006
DOI: 10.1111/j.1744-7909.2006.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Epidermal Cells: A Trap for Lipophilic Xenobiotics

Abstract: Plant surfaces are covered by a layer of cuticle, which functions as a natural barrier to protect plants from mechanical damage, desiccation, and microbial invasion. Results presented in this report show that the epicuticular wax and the cuticle of plant leaves also play an important role in resisting xenobiotic invasion. Although the epicuticular wax is impermeable to hydrophilic xenobiotics, the cuticle not only restricts the penetration of hydrophilic compounds into leaf cells, but also traps lipophilic one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…As the dominant form of Hg in the atmosphere (>95%) [26], Hg 0 is a mildly lipophilic compound [27] that could diffuse through the cuticle similar to volatile lipophilic compounds [28]. Moreover, compounds containing Hg(II)-either deposited to leaves from the atmosphere or produced at the leaf surface via Hg 0 oxidation [29]-could traverse the epocuticular dissolution into the underlying cuticle and diffuse to epidermal cells [30].…”
Section: Inorganic Hg In Tissues Of Rice Plants During the Rice-growimentioning
confidence: 99%
“…As the dominant form of Hg in the atmosphere (>95%) [26], Hg 0 is a mildly lipophilic compound [27] that could diffuse through the cuticle similar to volatile lipophilic compounds [28]. Moreover, compounds containing Hg(II)-either deposited to leaves from the atmosphere or produced at the leaf surface via Hg 0 oxidation [29]-could traverse the epocuticular dissolution into the underlying cuticle and diffuse to epidermal cells [30].…”
Section: Inorganic Hg In Tissues Of Rice Plants During the Rice-growimentioning
confidence: 99%
“…Nonstomatal processes are also important factors affecting Hg uptake by trees. Previous studies have demonstrated that Hg absorption to the epicuticular wax is directly influenced by the composition and properties of the epicuticular wax, which plays an important role in the Hg diffusion rate to epidermal cells and spatially across the leaf. Thicker wax, such as that on the celery top phyllodes, tends to result in less uptake of Hg. ,, Therefore, the waxy surface of celery top pine phyllodes may also prevent Hg entering its stomata and therefore contribute to its lower Hg uptake relative to huon pine.…”
Section: Resultsmentioning
confidence: 99%
“…60−62 Thicker wax, such as that on the celery top phyllodes, tends to result in less uptake of Hg. 60,63,64 Therefore, the waxy surface of celery top pine phyllodes may also prevent Hg entering its stomata 75 and therefore contribute to its lower Hg uptake relative to huon pine.…”
Section: Mercury Concentrations Between Speciesmentioning
confidence: 99%
“…4C) and low PSR (image not shown) showed turgid epidermis and with probable deposits of cuticular wax and microorganisms associated, contrasting with the images of epidermis from leaves of the plants from the medium PSR (Fig.4D) and upper PSR (images not shown), less turgid and apparently deprived of cuticular protection. Bytnerowicz et al (1998) Liu (2006), besides being a barrier to protect the plants from the mechanical damages, desiccation and microbial invasion, wax layers have an important role in resistance against the xenobiotics. Liu (2006) reported that, despite the impression given by guard-cells of an easy entrance point for xenobiotics, only a reduced portion of these xenobiotics from the leaf surface were able to enter through the stomatal aperture.…”
Section: Discussionmentioning
confidence: 99%